Pengaruh Kompetensi, Independensi, Profesionalisme, dan Peran Auditor Internal terhadap Pelaksanaan Good Corporate Governance - Azizah Nuraeni Budiningsih; Inayah Adi Sari; Abdulloh Mubarok (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
The purpose of this study is to determine the influence of competence, independence, professionalism, and the role of internal auditors on the implementation of Good Corporate Governance. The object of his research is BPR located in Central Java Region. The data were collected by using questionnaire method (primary) given to thirty internal auditors working in BPR. The analysis model used in this research is multiple linear regression analysis model which is done with the help of computer program SPSS version 23.0 for windows. The result of simultaneous research shows that the competence, independence, professionalism, and role of internal auditor have significant and significant effect on the implementation of good corporate governance proved by F = 76,975 significant 0,000 <0,05. Partially competence variable have positive and significant influence to the implementation of good corporate governance proved by significant value 0,005 <0,05, variable of independence have positive and significant influence to the implementation of good corporate governance proved with significant value 0,000 <0,05, professionalism variable have positive and significant to the implementation of good corporate governance is evidenced by significant value 0.000<0.05, the variable role of internal auditors have a positive and significant impact on the implementation of good corporate governance evidenced by significant value 0.042 <0.05.